(untitled) (International Journal of Engineering and Computer Science, 2017)
The security of the network reduces due to increase in the size of the network, there are many intrusion detection and intrusion response strategies which are carried on the basis to find and stop the intruders in the network such as local and global. Preserving the availability and integrity of networked computing systems in the face of fast-spreading intrusions requires advances not only in detection techniques and also in automated response techniques. Here a new concept of game theory using Stackelberg game is introduced along with the RRE (response and recovery engine) to provide the automated response by using ART trees. In the intrusion detection system, the intruders can be found automatically by the IDS alerts but the response is to be provided by the manual process with is based on the time constraint, in order to overcome this drawback, the intrusion response system is provided with automation